Prophylactic corticosteroid use prevents engraftment syndrome in patients after autologous stem cell transplantation. Issue 1 (3rd October 2020) - Betticher, Christophe; Bacher, Ulrike; Legros, Myriam; Zimmerli, Stefan; Banz, Yara; Mansouri Taleghani, Behrouz; Pabst, Thomas
Abstract: Engraftment syndrome (ES) following autologous stem cell transplantation (ASCT) at the time of neutrophil recovery may comprise fever, rash, pulmonary edema, or diarrhea. Usually, ES is easily manageable using corticosteroids but may prolong hospitalization. In two consecutive cohorts of subsequent patients with myeloma, lymphomas, and testicular/germ cell cancer, we assessed the benefit of corticosteroid use to prevent incidence and severity of ES following ASCT. Whereas Cohort A (82 patients) received no prophylactic corticosteroids, corticosteroids (4 mg dexamethasone oral daily) were started in Cohort B (60 patients) at day +9 until day +13 following ASCT. Steroid prophylaxis significantly reduced the incidence of ES (6/60; 10% vs. 33/82; 40%; p < 0.001). Hospitalization duration was longer in patients with ES than in patients without ES within both cohorts (in Cohort A: p = 0.007; and B: p = 0.011), but did not differ significantly between cohorts A and B. Finally, in Cohort A, there was a trend to an inferior 2‐year overall survival rate in patients without ES compared to patients with ES ( p = 0.067), but definite conclusions are not yet allowed. Our results suggest that corticosteroid prophylaxis from days +9 to +13 following ASCT significantly reduces the risk of ES and shortens hospitalization duration.